Analisis Kepuasan Pengguna Terhadap Penerapan Sistem Informasi Manajemen Puskesmas Di Puskesmas Sibabangun Menggunakan Metode EUCS Tahun 2023 - Deby Natalia Simatupang; Theofilus Zagoto (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2024)
Puskesmas services are progressing day by day, making them increasingly complex, therefore a puskesmas management information system is needed that is able to guarantee the availability of data quickly, accurately, up to date, continuously and responsibly. The community health center management information system (SIMPUS) is a community health center management application whose main function is as a tool for recording, processing and presenting information on all patient data from initial registration to reporting. Every Community Health Center is obliged to implement (SIMPUS) both electronic and non-electronic which is part of the health information system. One method used to evaluate the success of a system as seen from user satisfaction is End User Computing Statistics (EUCS). The EUCS definition of an information system itself is an overall evaluation of information system users with more emphasis on end user satisfaction (statisfaction) with 5 satisfaction assessment variables including content, format, accuracy, timeliness, ease of use. This research was conducted at the Sibabangun Health Center, Sibabangun sub-district, Central Tapanuli district in 2023, involving 30 respondents actively using SIMPUS with the EUCS method by sending questionnaires using Google Form to the respondents with the research results obtained being that on average respondents were satisfied with the implementation of SIMPUS but not closes the possibility that there are still many problems experienced by users, especially in the dimensions of accuracy and ease of use, with problems with system errors and ease of use which needs to be considered by providing training to all SIMPUS users.